Controlled Laboratory Comparison Study of Motion With Football Equipment in a Destabilized Cervical Spine: Three Spine-Board Transfer Techniques. Issue 9 (7th September 2015) - Prasarn, Mark L.; Horodyski, MaryBeth; DiPaola, Matthew J.; DiPaola, Christian P.; Del Rossi, Gianluca; Conrad, Bryan P.; Rechtine, Glenn R.
Background: Numerous studies have shown that there are better alternatives to log rolling patients with unstable spinal injuries, although this method is still commonly used for placing patients onto a spine board. No previous studies have examined transfer maneuvers involving an injured football player with equipment in place onto a spine board. Purpose: To test 3 different transfer maneuvers of an injured football player onto a spine board to determine which method most effectively minimizes spinal motion in an injured cervical spine model. Study Design: Controlled laboratory study. Methods: Five whole, lightly embalmed cadavers were fitted with shoulder pads and helmets and tested both before and after global instability was surgically created at C5-C6. An electromagnetic motion analysis device was used to assess the amount of angular and linear motion with sensors placed above and below the injured segment during transfer. Spine-boarding techniques evaluated were the log roll, the lift and slide, and the 8-person lift. Results: The 8-person lift technique resulted in the least amount of angular and linear motion for all planes tested as compared with the lift-and-slide and log-roll techniques. This reached statistical significance for lateral bending ( P = .031) and medial-lateral translation ( P = .030) when compared with the log-roll maneuver. The lift-and-slide technique was significantly more effective at reducing motion than the log roll for axial rotation ( P = .029) and lateral bending ( P = .006). Conclusion: The log roll resulted in the most motion at an unstable cervical injury as compared with the other 2 spine-boarding techniques examined. The 8-person lift and lift-and-slide techniques may both be more effective than the log roll at reducing unwanted cervical spine motion when spine boarding an injured football player. Reduction of such motion is critical in the prevention of iatrogenic injury.